2019
DOI: 10.33145/2304-8336-2019-24-261-269
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Combined Action of X-Radiation and Cyclooxygenase-2 – Meloxivet Inhibitor on Vegf and Pge-2 Content in Blood of Rat-Tumor Carriers

Abstract: Мета: вивчення впливу комбінованої дії Х випромінення та інгібітора циклооксигенази 2 (ЦОГ 2) на рівень фактора росту ендотелію судин (VEGF) і простагландину E 2 (PGE 2) 2 в сироватці крові щурів з перевитою пух линою Герена при опроміненні в різних дозах. Матеріали і методи. 20 щурам самицям популяції Вістар масою 160-180 г з перещепленою карциномою Гере на проводили фракціоноване опромінення (5 Гр + 5 Гр) та (0,5 Гр + 0,5 Гр) зони росту пухлини на апараті РУМ 17 з інтервалом між сеансами 24 год. Препарат «Ме… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…A study showed that the levels of VEGF in the blood of rats were down-regulated 3.49 fold after 10 Gy irradiation, which implies that the inhibition of angiogenesis hinders wound healing. 34 The ability of EG-CHI-GEL-MA hydrogel to promote the expression of these genes and cytokines suggests that it has a good pro-vascular repair function in the skin.…”
Section: Resultsmentioning
confidence: 99%
“…A study showed that the levels of VEGF in the blood of rats were down-regulated 3.49 fold after 10 Gy irradiation, which implies that the inhibition of angiogenesis hinders wound healing. 34 The ability of EG-CHI-GEL-MA hydrogel to promote the expression of these genes and cytokines suggests that it has a good pro-vascular repair function in the skin.…”
Section: Resultsmentioning
confidence: 99%
“…Radiation-activated COX-2 can induce the production of prostaglandin H2 (PGH2). Following this, PGH2 triggers thromboxane A2 (TXA2) and promotes vascular growth ( Mitryayeva et al, 2019 ; Anoopkumar-Dukie et al, 2020 ). Radiotherapy was also shown to activate production of prostaglandin E2 (PGE2) which promotes the expression of HIF-1α and VEGF ( Kovacs et al, 2019 ).…”
Section: Radiation Therapy Effects In Tumor Vasculaturementioning
confidence: 99%